Analysis of the Rice Entrepreneurship System on the Income of the Bulog Kansilog in Bone Regency - Kurnia, Irma; Musfira, Ria; Harisa, Harisa (LPPM Universitas Muhammadiyah Mamuju, 2024)
Bulog is a state-owned public company that operates in the food logistics sector. Bulog has systems for carrying out relationships with companies through contracts, with prices stated in them. The type of research used is qualitative research, namely research that is descriptive in nature and tends to use analysis. The data collection techniques used are observation, interviews and documentation. The results of the research show that: The contract system used is in line with the sale and purchase of goods which are stated to be covered, including the parties involved, the price mentioned in the contract, the object of the goods being bought and sold, as well as the agreement that has been established between the entrepreneur and Bulog.